The Management of Patients with Extrapulmonary Sarcoidosis in Rheumatology Clinic - Gülle, Semih; Ataca, Mert Can; Sarı, İsmail; Birlik, Merih; Can, Gercek; Önen, Fatoş (Aktuelle Rheumatologie, 2024)
Background This study aimed to evaluate patients with extrapulmonary and refractory sarcoidosis who were followed up on in our rheumatology clinic for a long follow-up period and to summarise the applications in rheumatology practice.Materials and Methods The study included patients diagnosed with sarcoidosis at our institution between 2010 and 2022. Patientsʼ age, sarcoidosis diagnosis dates, inflammatory rheumatic disease (iRMD) diagnoses, autoimmune markers, and imaging findings were all evaluated. Estimates were made for cases of glucocorticoid (GC) use and cumulative and mean daily GC exposures.Results 90 patients with sarcoidosis, 79 (87.8) female and 11 (12.2) male, whose mean age was 56.4±12.4 years, were included. Since 48 (53.3%) of the patients required at least one additional treatment in addition to CS, they were classified as having refractory sarcoidosis and followed up accordingly. While 43 (89%) of the patients received second-line sarcoidosis treatment, it was found that 5 patients were switched to third-line sarcoidosis treatment (p<0.001). Comorbidity distributions of refractory and nonrefractory patients were similar. It was determined that 9 (10%) patients had a history of osteoporotic fracture.Conclusions In conclusion, it appears critical to develop a detailed patient management plan and a multidisciplinary approach in the early stages of extrapulmonary sarcoidosis management. There is currently no detailed algorithm covering refractory disease definition and treatment practice differences.
Keywords: sarcoidosis; glucocorticoid; iRMD; osteoporosis; TNFi